Impacts of Breed, Production System and Feeding Type on Nutritional, Organoleptic Characteristics and Oxidative Status on Beef Cattle in Sub-Saharan Africa: A Cross-Sectional Study - Youmbi Kammogne Ivana Gilberte Cyrielle; Célestin, Godwe; Djeunga, Nana Hugues; Ndjengue Mindang Elisabeth Louise; Edoun Ebouel Ferdinand Lanvin; Magloire, Feugang, Jean; Djiogue, Sefirin (American Journal of Food Sciences and Nutrition, 2024)
Purpose: The aim of this study was to investigate the influence of breed, production system, and feeding type on meat quality, evaluating organoleptic and physicochemical traits and antioxidant status across selected local cattle breeds. Materials and Methods: The study was carried out on sirloin and blood samples taken in slaughterhouses from the hot carcass of male cattle, divided according to breed, production system and type of feed. The nutritional, organoleptic characteristics and oxidative status was assessed. Findings: The results revealed that meat from Goudali breed raised in a sedentary system exhibited significantly lower tenderness (p<.) and higher lipid (p<.) and protein (p<.) contents. Additionally, the meat displayed notably lower pH (p=.), reduced cortisol (p<.), and lower catalase (p<.), TAC (p<.), and FRAP (p=.) activities. Consumers preferred the meat of the White Fulani breed due to its color (p<.). In transhumant system, the meat was richer in dry matter (p=.), lipids (p<.), and fibres (p=.), while the sedentary system resulted in more tender (p=.) and red-dark colored meat (p<.), which consumers favored. Meat from cows under commercial feed were preferred by consumers (p<.) compared to grass-fed cows, exhibiting significantly higher lipid (p<.) and protein (p<.) levels as well as intense color (p=.). However, meat from grass-fed cows had significantly higher fibre content (p<.), tenderness (p<.), better taste (p=.), juiciness (p=.), and higher catalase (p=.) and TAC (p<.) activities. Implications to Theory, Practice and Policy: These findings underscore the importance of considering breed, production system, and feeding type when conserving, selecting, or improving beef breeds for both meat quantity and quality.